2020
DOI: 10.1002/ppap.202000207
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of plasma‐processed air for biological decontamination of crop seeds on the premise of unimpaired seed germination

Abstract: In this study, the antimicrobial effect of plasma‐processed air (PPA) generated by a microwave‐induced nonthermal plasma was investigated for preharvest utilization using three crop species: Barley, rape, and lupine. Bacillus atrophaeus spores were chosen as a model, inoculated onto seeds, and subsequently treated with PPA at two different flow rates, different filling regimes, and gas exposure times. PPA treatment was efficient in reducing viable spores of B. atrophaeus, reaching sporicidal effects in all spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…However, Hthis is not the only problem with plasma treatment. Sometimes, the exposure time necessary for pathogen inactivation is too long and also causes damage to seeds, resulting in lower germination, as was shown in previous studies [ 24 , 25 ]. It was shown that longer exposure of seeds to plasma can cause serious damage to seed morphology that leads to reduced germination.…”
Section: Introductionmentioning
confidence: 95%
“…However, Hthis is not the only problem with plasma treatment. Sometimes, the exposure time necessary for pathogen inactivation is too long and also causes damage to seeds, resulting in lower germination, as was shown in previous studies [ 24 , 25 ]. It was shown that longer exposure of seeds to plasma can cause serious damage to seed morphology that leads to reduced germination.…”
Section: Introductionmentioning
confidence: 95%
“…Barley (Hordeum vulgare) seeds' treatment with microwave-driven Air plasma showed a negative effect on maximum germination [79], while barley seeds treated with lowpressure (26 Pa) plasma had no effect on the germination [81], whereas treatment with surface dielectric barrier discharge (SDBD) plasma resulted in the early growth of barley sprouts [80]. The increase in early growth and fresh weight of barley sprouts was due to improved levels of the primary metabolites (soluble sugars and free amino acids) and secondary metabolites (saponarin, GABA, and policosanols) [80].…”
Section: Maize (Zea Mays)mentioning
confidence: 99%
“…In the work [71], unusual plasma-processed air (PPA) was used for inactivation of B. atrophaeus (DSM 675) endospores on barley grains, where gas flows from the active plasma to the incubation bottles. The number of spores was reduced from the initial concentration of ~10 6 CFU/per 10 g by 3.00 ± 0.33 log 10 after 3 min of exposure.…”
Section: Barleymentioning
confidence: 99%